Understanding the Link Between Motivational Interviewing and Self-Compassion - Pastore, Olivia; Fortier, Michelle (Canadian Journal of Counselling and Psychotherapy, 2020)
In this article, the authors posit that the accepting and compassionate spirit of motivational interviewing (MI), along with specific content-based techniques (i.e., reframing), can help to cultivate a self-compassionate mindset within clients receiving MI. The authors explore this link further while discussing potential moderators that may influence this process as well as practical implications for counselling practice and future research recommendations. This article is innovative in that it could provide a new theoretical foundation for conducting research that supports the effectiveness of MI in enhancing self-compassion, which has been associated with a myriad of improved psychological outcomes. The concepts of this paper and the exploration between specific MI techniques would be valuable to many clinicians with the desire to increase self-compassion in their clients.